The Relation Between Inflation and Export Prices: An Aggregate Study - M.F.J. Prachowny (Queen's University, Department of Economics, 1970)
One of the alleged costs of inflation is said to be the loss of competitiveness in international markets if the rate of change of proces is higher in the domestic country than in the rest of the world. While inflation is measured by changes in the consumer price index, wholesale price index, or the implicit deflator of GNP, competitiveness in this context is determined by changes in the export price index in one country in relation to price changes in other countries.
Keywords: 330